1990
DOI: 10.1002/art.1780330826
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐D Region genes associated with autoantibody responses to histidyl‐transfer RNA synthetase (Jo‐1) and other translation‐related factors in myositis

Abstract: Myositis has been associated with HLA-B8 and DR3, especially in white patients with polymyositis and serum anti-Jo-1 antibodies. Twenty-eight patients with myositis and serum translation-related autoantibodies anti-Jo-1, anti-PL-7, anti-PL-12, anti-KJ, and anti-SRP were studied for HLA class I1 specificities by Southern blotting with HLA-DRP, DQP, and D Q a probes. The association of HLA-DR3 (DRwl7) with anti-Jo-1 antibodies in white myositis patients was confirmed (P = 0.003, relative risk 8.9). However, HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 49 publications
1
21
0
1
Order By: Relevance
“…The association of anti-Jo-1 antibodies and alleles comprising the 8.1 haplotype has been confirmed in several studies [11,13,29-31]. This strong relationship between HLA and serological subtype is also present for other MSAs/MAAs, in which antibodies other than anti-Jo-1 are associated with other haplotypes.…”
Section: Hla Associations With Myositis Autoantibodiesmentioning
confidence: 57%
“…The association of anti-Jo-1 antibodies and alleles comprising the 8.1 haplotype has been confirmed in several studies [11,13,29-31]. This strong relationship between HLA and serological subtype is also present for other MSAs/MAAs, in which antibodies other than anti-Jo-1 are associated with other haplotypes.…”
Section: Hla Associations With Myositis Autoantibodiesmentioning
confidence: 57%
“…In our case, the sequence of the first 60 amino acids of HisRS (UniProtKB identifier P12081) was examined to predict peptides that can bind DRB1*03:01; residues 11-23 (HisRS 11-23 ) contained 2 such motifs and therefore had a high probability of containing a bona fide DRB1*03:01 epitope. Thus, HisRS [11][12][13][14][15][16][17][18][19][20][21][22][23] peptide was selected for further functional assays ( Figure 1A). Immunohistochemistry and histopathology.…”
Section: Identification Of the Hisrs T Cell Epitopementioning
confidence: 99%
“…To identify the potential presence of antigen-specific T cells against HisRS in the blood of patients with IIM/antisynthetase syndrome, we assessed the up-regulation of CD40L in CD4+ T cells following stimulation with HisRS protein or HisRS [11][12][13][14][15][16][17][18][19][20][21][22][23] After stimulation of PBMCs with HisRS 11-23 , we detected up-regulation of CD40L on CD4+ T cells in 11 of 14 patients with IIM/antisynthetase syndrome, with a median fold change of 3.4 (IQR 1.87-10.9) relative to unstimulated cells (P = 0.0012). The highest response toward HisRS 11-23 (>10-fold change versus unstimulated cells) was observed in 3 of 11 patients with IIM/ antisynthetase syndrome (2 anti-Jo-1+ and 1 anti-Jo-1−), with a median fold change of 12.75 (IQR 10.9-37) ( Figures 1B and C).…”
Section: Presence Of Hisrs-t Cell Reactivity In the Peripheral Blood mentioning
confidence: 99%
See 1 more Smart Citation
“…In PM/DM, complication with ILD is associated with the anti-aminoacyl-transfer RNA synthetase (anti-aaRS) antibody or anti-MDA-5 antibody. It has been reported that 90% of Caucasian patients with the anti-aaRS antibody are carriers of HLA-DRB1*03 (7). In the Japanese population, HLA-DRB1*0405 is associated with susceptibility to anti-aaRS antibody-positive PM/DM (8).…”
mentioning
confidence: 99%